Predicting Body Height in a Pediatric Intensive Care Unit Using Ulnar Length - Rasouli, Melody A.; Newth, Christopher J. L.; Khemani, Robinder G.; Ross, Patrick A. (Frontiers in Pediatrics, 2018)
Objective: To determine if ulnar length obtained by the bedside nurse can be used to estimate patient length. To compare our findings to previous predictive equations of height and ulnar length. To evaluate the performance of predictive equations for height and ulnar length on patients with syndromes that affect height. Design: Retrospective observational study of prospectively collected data Settings: Multidisciplinary Pediatric Intensive Care Unit in a university teaching hospital Patients: 1,177 patients, ages 1 month to 23 years. Mean age was 79.7 months (1,3 IQR 19.5, 164.5 months) and 55.4% male. Measurements: Ulnar length was obtained using digital calipers by bedside nurses in PICU as well as height and weight. The electronic health care record was used to extract patient information. Main Results: The predictive equation for height for the entire group is: height (cm) = 0.59*ulnar length (mm) + 13.1 (r2=0.93). Bland Altman analysis of the derivation formula applied to the testing group did not show any systematic bias. Conclusions: Our study shows that ulnar length measurements can be used to predict height with a simple linear formula in a PICU setting. Not having specific individuals or specific training for ulnar measurement did not seem to alter the accuracy (r2= 0.93). The robust nature of the measurement and ease of use may make this an unconventional but reasonable alternative to obtaining height when that cannot be measured directly.